2018
DOI: 10.1016/j.bmc.2018.07.029
|View full text |Cite
|
Sign up to set email alerts
|

Small molecule scaffolds that disrupt the Rev1-CT/RIR protein-protein interaction

Abstract: Translesion synthesis (TLS) is a DNA damage tolerance mechanism that allows replicative bypass of DNA lesions, including DNA adducts formed by cancer chemotherapeutics. Previous studies demonstrated that suppression of TLS can increase sensitivity of cancer cells to first-line chemotherapeutics and decrease mutagenesis linked to the onset of chemoresistance, marking the TLS pathway as an emerging therapeutic target. TLS is mediated by a heteroprotein complex consisting of specialized DNA polymerases, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…One strategy to inhibit TLS for chemotherapeutic sensitivity is to disrupt essential PPIs that control assembly of the multiprotein TLS complex with small molecules [9,29–33] . Our attempts to inhibit TLS focused on blocking PPIs of Rev1‐CT with RIR motifs from Polη, Polι, Polκ, and PolD3.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One strategy to inhibit TLS for chemotherapeutic sensitivity is to disrupt essential PPIs that control assembly of the multiprotein TLS complex with small molecules [9,29–33] . Our attempts to inhibit TLS focused on blocking PPIs of Rev1‐CT with RIR motifs from Polη, Polι, Polκ, and PolD3.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of contacts between Rev1‐CT and RIR are mediated by the FF pair and mutation of these residues completely abrogates the PPI [23–25] . We have used biochemical high‐throughput screening, [29–30] virtual screening, [32] and rational design approaches [31] to identify small molecules that disrupt Rev1‐CT/RIR PPIs. The identified scaffolds demonstrated concentration‐dependent displacement of FAM‐Polκ‐RIR peptide from its complex with Rev1‐CT in fluorescence polarization and/or intensity (FP/FI) assays, as well as direct binding to the RIR site on Rev1‐CT in NMR titration experiments.…”
Section: Introductionmentioning
confidence: 99%
“…[1,2,8,9] Severalo ft hese switching events are mediated by protein-protein interactions (PPIs) between the C-terminal domain of the Y-familyp olymerase Rev1 (Rev1-CT) and the Rev1 interacting regions (RIR) from the Y-familyp olymerases polh,p olk,p oli,a nd polz. [14][15][16] These compounds increase sensitivity to cisplatin and decrease cisplatin-mediated mutagenesis in human cancer cells, highlighting their potential as combination therapies for variousforms of cancer. [14][15][16] These compounds increase sensitivity to cisplatin and decrease cisplatin-mediated mutagenesis in human cancer cells, highlighting their potential as combination therapies for variousforms of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13] We recently identified the first small molecules( Figure1A, 1 and 2)t hat disrupt the Rev1-CT/ RIR PPI. [14][15][16] These compounds increase sensitivity to cisplatin and decrease cisplatin-mediated mutagenesis in human cancer cells, highlighting their potential as combination therapies for variousforms of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies demonstrate that the noncatalytic function of Rev1 relies on Rad5, that the C terminus of Rev1 physically interacts with the N terminus of Rad5, and that blocking this interaction inactivates the noncatalytic activity of Rev1, but not the transferase activity (21,22). Recent work has revealed that Rev1 acts as a scaffold protein interacting with other TLS polymerases (23,24). In S. cerevisiae and human cells, Rev1 promotes Pol recruitment through physical interaction with it when DNA is damaged (25)(26)(27), and Rev1 forms a complex with Pol to bypass thymine dimers induced by UV irradiation (28).…”
mentioning
confidence: 99%